Impacto de la atención farmacéutica en el cumplimiento de la farmacoterapia antimicrobiana prescrita a los pacientes con infección de vías urinarias - Caballero Aquiño, Olga Elizabeth (2014)
The purpose of the study was to determine the impact of pharmaceutical care on adherence to antimicrobial drug indicated for patients with urinary tract infection (UTI). The experimental design included two randomized groups, assigning each group 18 patients with confirmed bacteriological diagnosis of UTI and prescribed antimicrobial drug, raised in a community pharmacy. The intervention group received pharmaceutical care notarized and received over traditional pharmaceutical assistance. Then both groups were evaluated and tested for verification of compliance with antibiotic therapy. The results showed significant differences (p= 0,015) in adherence to treatment according to the Morisky-Green-Levine, being higher in the intervention group with 83% adherence and 44% in the control group. The tablet count test also showed significant differences (p = 0,007) in adhesion, 94% for the surgical group and 56% for control. We conclude that pharmaceutical care protocolized has a positive impact more on compliance with antimicrobial therapy traditional care.